On gender inequality and life satisfaction: does discrimination matter? - Bjørnskov, Christian; Dreher, Axel; Fischer, Justina A. V. (KOF working papers, 2007)
This paper analyzes the impact of gender discrimination on individual life satisfaction using a cross-section of 66 countries. We employ measures of discrimination of women in the economy, in politics, and in society more generally. According to our results, discrimination in politics is important to individual well-being. Overall, men and women are more satisfied with their lives when societies become more equal. Disaggregated analysis suggests that our results for men are driven by the effect of equality on men with middle and high incomes, and those on the political left. To the contrary, women are more satisfied with increasing equality independent of income and political ideology. Equality in economic and family matters does overall not affect life satisfaction. However, women are more satisfied with their lives when discriminatory practices have been less prevalent in the economy 20 years ago. -- Gender gap ; happiness ; well-being ; discrimination ; life satisfaction
Erscheinungsjahr in Vorlageform:Apr. 2007
Keywords: Arbeitspapier; Graue Literatur